Executive Dysfunction Associated With the Primary Psychopathic Features of Borderline Personality Disorder - López-Villatoro, José M.; Diaz-Marsá, Marina; Mellor-Marsá, Blanca; De la Vega, Irene; Carrasco, José L. (Frontiers in Psychiatry, 2020)
Purpose: The aim of the present study is to investigate whether the presence of psychopathic features in BPD is related to dysfunction in executive functions and other neuropsychological functions in these patients. Methods: 82 patients diagnosed with borderline personality disorder and 54 control subjects were studied through clinical and neuropsychological evaluation protocols and the Levenson Psychopathy Inventory. Results: BPD patients showed significantly higher scores on both primary (F1) and secondary (F2) global rates of psychopathy, than controls. The results for these patients also showed a statistically significant association between high scores in primary psychopathy and deficits in executive functions. However, no associations were found between the scores of secondary psychopathy and executive dysfunction. Conclusion: Primary psychopathic features present in patients with BPD are associated with patterns of executive dysfunction. It would therefore be interesting to investigate the role of cognitive rehabilitation in the empathy dysfunctions within these disorders.